Finite element modelling and optimization of microlattice structure - Toh, Yi Cong (2016)
The advancements in 3D printing technologies have resulted in the ease of manufacturing cellular microlattice structures. Cellular lattices offer superior mechanical properties including high strength-to-weight ratio, high stiffness-to-weight ratio, as well as other high thermal and energy absorption. Hence, microlattice structures could be utilized in various industries such as bioengineering, automobile and aerospace industries. This research paper focuses on exploring different unit cell topologies and examining the effect on their mechanical behavior. A total of 12 different unit cell topologies are studied and modelled using SolidWorks and ABAQUS (Finite Element software). The topologies are modelled at 3 different relative densities between 6-11%. Each lattice made up of 3 by 3 by 3 unit cells are simulated under a uniaxial compression and evaluated based on its stiffness and energy absorption capacity. The lattices are classified according to their deformation mechanisms, and the trends of the mechanical performance of the lattices are discussed. Modifications are recommended and similarly modelled to optimize the stiffness of the lattice. No experimental work was undertaken. The project aims to provide an optimized unit cell topology and to serve as a guide for future work in designing a unit cell for light weight applications.